Pendampingan Terpadu untuk Meningkatkan Kesadaran Pendidikan bagi Penerima PKH di Kecamatan Mlandingan Situbondo - Achmad Suhaili (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
This community service program aims to raise educational awareness among the beneficiaries of the Family Hope Program (PKH) in Mlandingan District, Situbondo Regency, through the implementation of the Parent School. The Participatory Action Research (PAR) method is used to ensure the active involvement of the community in the service process. PAR is implemented in three main stages: planning, action, and reflection. In the planning stage, the service team collaborates with the community to design a program that is relevant and meets their needs. In the action stage, training and outreach are provided to parents on the importance of education and how to support their children's academic development. In the reflection stage, an evaluation of the program’s impact is conducted, and steps for improvement are identified for the future.This program covers five priority villages with low levels of education and human resources. A total of 1,336 parents who are beneficiaries of the PKH program participated. The results show an increase in parental awareness of the importance of education, with 75% of parents now regularly accompanying their children in their studies, compared to only 15% before the program. Additionally, 25 parents successfully enrolled their children in higher education through the KIP program and regional scholarships. The program has also strengthened collaboration between parents and educational institutions, with 70% of parents now more actively discussing their children's education. Increased community participation in supporting children's academic development proves that this program is effective in strengthening family relationships and improving education quality in the area. Recommendations for the continuation of this program include expanding the scope and frequency of training for parents, as well as providing more information about scholarship opportunities and educational pathways. Additionally, stronger efforts are needed to integrate this program with local educational policies to support its sustainability in the long term. It is hoped that this program can become a sustainable model for breaking the cycle of poverty through education, involving more communities in areas with similar challenges.